Positioning the Voice and Agency of Young Children in the Distance Education of the Sami Languages - Helander, Hanna; Keskitalo, Pigga; Turunen, Tuija (Multiethnica: Journal of the Hugo Valentin Centre, 2023)
This article examines the agency and voices of children aged six and seven who study the endangered Indigenous Sami languages Northern, Skolt and Inari Sami through distance education in Finland. While ensuring the agency and voices of children, this article addresses connections between microlevel actions in online teaching and, more widely, the surrounding sociopolitical context. About 75% of Sami-speaking children under the age of 10 live outside the Finnish Sami homeland, while the Basic Education Act secures teaching in Sami languages only within the homeland. Outside this region, children can participate in teaching for two hours per week as an extracurricular activity. The data is drawn from children’s interviews (N=10) conducted in spring 2020. Due to the Covid-19 pandemic, interviews were conducted online, mainly as group interviews, but individual interviews were also conducted. The findings indicate that despite the challenging learning context of distance education, children with diverse linguistic backgrounds were highly motivated to learn Sami languages and connect to their Sami backgrounds through an integral motivation strategy. Despite receiving varying levels of support at society, at home and at school, there was a strong relational intergenerational connectivity fostered between parents and children through Sami language learning.